SIFOEDT (Simple Foot Elevator For Diabetic Ulcer Treatment) - Abdul Majid; Agus Sarwo Prayogi; Surantono Surantono; Sri Hendarsih (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2017)
In the world, the number of people with diabetes is estimated to 171 million people and is predicted to reach 366 million in 2025. The increase in DM patients, the diabetic ulcer complications have also increased, which is about 15% suffer from ulcers in the legs, and 12-14% including foot ulcers require amputation. The results of field studies showed that treatment of diabetic ulcers in hospitals prior to this innovation is to drape the foot side of the bed; stuck in bed with the coated; placed on crooked, and there are propped up with plastic basin. This causes the treatment time becomes longer, discomfort, fatigue and difficult during treatment of diabetic ulcers. Objective: Creating a tool that can be used for treatment of diabetic ulcers more effectively and efficiently, that is SIFOEDT (Simple Foot Elevator for Diabetic Ulcer Treatment). Methods: Quasi-experimental, with pre and post test without control group design, with a sample size of 30 respondents consisting of 15 respondents at Sleman District Hospital and 15 respondents at Panembahan Senopati Hospital, Bantul. Sampling Technique used consecutive sampling. Results: Mean of ulcer treatment before using Sifoedt was 18.09 minutes, and after using Sifoedt was 12.62 minutes. Before using Sifoedt, majority (80%) said less comfortable, while after using Sifoedt majority (90%) said comfortable. The level of fatigue patients before using Sifoedt showed majority (86.7 %%) said fatigue, while after using Sifoedt majority (93.3%) said no fatigue. Conclusions: There are significant differences of diabetic ulcer treatment time before and after using Sifoedt (p = 0.000). There are significant differences in comfort of patients before and after using Sifoedt (p = 0.000). And there are significant differences in fatigue before and after using Sifoedt (p = 0.000).